(untitled) ("Journal "U". Economy. Management. Finance.", 2026)
The article examines the role of the Bank of Russia in ensuring the stability of the Russian Federation’s monetary system. It investigates key regulatory areas, including maintaining ruble stability, developing the banking and payment systems, and incorporating ESG factors as an additional tool for strengthening financial stability. Special attention is given to the importance of monetary policy and banking regulation in shaping a stable and predictable financial and economic environment.